Synthesis and Complexation of New Unsymmetrical 1,2-Dihydroxyimino-3,6-Diaza-7-Phenylheptane - Şekerci, M. (IAPC Nauka/Interperiodica, 2000)
1-Amino-2-(N-benzylamino)ethane (1) has been obtained by the reaction of benzyl chloride and ethylenediarnine. In a second step, 1,2-dihydroxyimino-3,6-diaza-7-phenylheptane (2) has been obtained by the reaction of (1) with anti-chloroglyoxime. The resulting 1,2-dihydroxyimino-3,6-diaza-7-phenylheptane ligand was reacted with transition metals such as Ni(II), Co(II) and Cu(II). The Cu(II) and Ni(II) complexes of these ligands are proposed to be square-planar, while the Co(II) complexes are proposed to be octahedral with water molecules as axial ligands. The structures of the new materials were identified by using elemental analyses, IR and 1 H NMR spectra, magnetic measurements, and TGA and DTA techniques.